Urban Family Migration and Economic Livelihoods of Migrants in Colombo District, Sri Lanka - Manel, D. P. K. (My University, 2022)
Globally, there are numerous types of migrations in the internal migration process. Most of the internal migration studies have focused on individual migration than family or household level migration and their social and economic livelihoods. Therefore, this study explores the reasons for urban family migration and their status of economic livelihoods. The study uses the quantitative method to gather information and utilizes data from the Population and Housing Census, 2012 in Sri Lanka and primary data collected in 2015-2016 from the Municipal Council and Urban Council areas in the Colombo district in Sri Lanka. The unit of analysis is the migrant household. The Chi-square test and Contingency Coefficient were applied to examine the factors which influence family migration to urban areas and their economic livelihoods in the destination areas. A composite index was constructed using the PCA method to analyse the quantitative data. The findings of the study reveal that approximately two-thirds (60.79%) of families have migrated to urban areas in the Colombo district due to their children’s educational attainments. The majority of migrant families in the study have migrated due to easy access to non-agricultural employment opportunities, good education facilities, public services and opportunities to utilize other infrastructure facilities available in the urban locations The findings may assist policymakers and planners to implement new policies or making necessary changes to existing policies so as to reduce the urban migration in highly urbanized areas in the capital city of the country.
Keywords: Economic livelihoods, Family migration, Sri Lanka